Effect of financial factors and optimum currency area on real exchange rate in ASEAN-3 countries - Tiang, Din Pian (2013)
Regional integration has become important subject among economists and is viewed capable of boosting monetary cooperation and foreign exchange arrangements among ASEAN-3 members thus promotes greater macro coordination, with the ultimate goal of reducing the extent of macroeconomics, such as real exchange rate. The purpose of the formation is to reduce exchange rate uncertainty and to avoid exchange rate misalignment among the ASEAN member countries. This research intends to investigate the extent of optimum currency area (OCA) variables and financial factors (FF) works within the context of ASEAN-3 countries with US Dollar used as anchor currencies, given their importance being major trading partners with the ASEAN countries and being the global demand currencies. In general, we found that several financial factors were found to have significant contribution on determining exchange rate variation. In addition, OCA variables have played an important role in explaining the bilateral real exchange rate